A New Generation Method for Spatial-Temporal Correlated MIMO Nakagami Fading Channel - Qiu-Ming Zhu; Xiang-Bin Yu; Jun-Bo Wang; Da-Zhuan Xu; Xiao-Min Chen (International Journal of Antennas and Propagation)
A new generation method for spatial and temporal correlated multiple-input multiple-output (MIMO) Nakagami fading channel is proposed, which has low complexity and is applicable for arbitrary fading parameters and prespecified correlation coefficients of different subchannel. The new scheme can be divided into two steps: (1) generate independent Nakagami fading sequences for each subchannel based on a novel rejection method; (2) introduce the temporal and spatial correlation based on the relationships between Rayleigh, Gamma, and Nakagami random processes. The analysis and simulation results show that the proposed simulator has a good agreement with the theoretical model on fading envelope distribution, spatial-temporal correlation characteristic.